Habitus of Recipients of the Family Hope Program (PKH) Social Assistance: A Case Study in Sidoharjo Village - Bintang Suci Maharani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study is motivated by the high poverty rate in Pacitan Regency and the low graduation rate of beneficiaries of the Family Hope Program (PKH), indicating problems not only in economic aspects but also in social and cultural dimensions. This research aims to analyze how the habitus of poverty shapes the behavioral patterns of PKH recipients in managing social assistance. The study employs a qualitative approach with a phenomenological method, using in-depth interviews, observation, and documentation techniques. Data analysis is conducted interactively using the habitus theory perspective of Pierre Bourdieu. The results show that beneficiaries tend to have a survival-oriented mindset, use assistance for short-term needs, and experience dispositional conflicts within their social capital. The habitus of poverty also reproduces intergenerational dependency and dominates the effectiveness of program interventions. In conclusion, social assistance has not fully succeeded in fostering independence due to the strong influence of habitus that shapes the recipientsâ€™ mindset and daily practices. Â